World encyclopedia of police forces and correctional systems - Kurian, George Thomas; Kurian, George Thomas; Gale Group (Detroit, Mich. Gale, 2006)
This fully updated version of the original 1989 edition of the World Encyclopedia of Police Forces and Correctional Systems describes the national law enforcement and correctional systems of more than 195 countries across the globe.
Volume 1. Introduction -- Acknowledgements -- List of articles -- About the contributors -- Chronology of international policing -- Overviews -- Countries: A-L -- Volume 2. Countries: M-Z -- List of appendixes -- List of police codes of ethics -- Police codes of ethics -- Text acknowledgements -- Police origins worldwide -- Police rankings -- General bibliography -- Index.
Rev. ed. of: World encyclopedia of police forces and penal systems / George Thomas Kurian. c1989.
Electronic reproduction.
Keywords: Police -- Encyclopedias; Corrections -- Encyclopedias; Criminal law -- Encyclopedias; Electronic books